Anticipatory Baseline Pupil Diameter Is Sensitive to Differences in Hearing Thresholds - Ayasse, Nicolai D.; Wingfield, Arthur (Frontiers in Psychology, 2020)
Task-evoked changes in pupil dilation have long been used as a physiological index of cognitive effort. Unlike this response, that is measured during or after an experimental trial, the baseline pupil dilation (BPD) is a measure taken prior to an experimental trial. As such, it is considered to reflect an individual’s arousal level in anticipation of an experimental trial. We report data for 68 participants, ages 18 to 89, whose hearing acuity ranged from normal hearing to a moderate hearing loss, tested over a series 160 trials on an auditory sentence comprehension task. Results showed that BPDs progressively declined over the course of the experimental trials, with participants with poorer pure tone detection thresholds showing a steeper rate of decline than those with better thresholds. Data showed this slope difference to be due to participants with poorer hearing having larger BPDs than those with better hearing at the start of the experiment, but with their BPDs approaching that of the better hearing participants by the end of the 16o trials. A finding of increasing response accuracy over trials was seen as inconsistent with a fatigue or reduced task engagement account of the diminishing BPDs. Rather, the present results imply BPD as reflecting a heightened arousal level in poorer-hearing participants in anticipation of a task that demands accurate speech perception, a concern that dissipates over trials with task success. These data taken with others suggest that the baseline pupillary response may not reflect a single construct.